Chronicles of our time - Beteille, Andre (New Delhi Pengin Books, 2000)
Chronicles of our time begins with the subject of the individual's quest for identity. It is thought-provoking and insightful essays on the state of the nation.Author outlines the contradictions inherent in the Indian context between the ideal of equality
Keywords: English essays; India-Politics and government; Education, Higher-Essays